An Analysis on the Effects of NPL, NIM, LDR on Profitability Level and Stock Returns in Conventional Banks Listed in the Main Board of Indonesia Stock Exchange in The Period of 2014-2018 - Oktary, Dewi; Pratiwi, Rurin (Universitas Muhammadiyah Sorong, 2021)
To find out the effects of NPL, NIM, LDR on the profitability level and stock returns is the aim of this study. The samples used were 24 conventional banks listed on IDX main board in 2014- 2018. The techniques of data analysis were path analysis and Sobel test. The results obtained in this study were that NPL had a significant negative effect on profitability and stock returns, NIM had a significant positive effect on the profitability level and stock returns, while LDR had no significant effect on the profitability level but it had a significant negative effect on stock returns. Profitability level had no significant effect on stock returns. NPL, NIM, LDR simultaneously had a significant effect on profitability. In addition, NPL, NIM, LDR and Profitability Level simultaneously had a significant effect on stock returns. NPL, NIM, LDR had no significant effect on stock returns. NPL, NIM, LDR had no significant effect on stock returns through profitability.Â